Protonated layered iridium oxide H-IrO2 nanosheet as well as preparation method and application thereof
Through the fast and mild scorched ear heating and proton exchange process prepared by the proton layer-like oxidation H-IRO2 nanometer, it solves the problem of difficulty and balance between the activity and stability of the oxidation catalyst in the existing technology, and realizes high-efficiency and stable electrochemical chemistry Analysis of oxygen reaction.
Patent Information
- Application Number
- CN202411476749.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-10-22
AI Technical Summary
The prior art is difficult to achieve a balance between the activity and stability of iridium oxide catalysts in an acidic environment, resulting in insufficient catalytic activity or poor stability during water electrolysis.
By using the rapid and gentle coking ear heating process, combined with proton exchange process, prepare a proton-shaped layer-shaped oxide H-IRO2 nanometer with long-range orientation and local disorderly defects.
A medium-efficient catalysis of the oxygen analysis of the electrified oxygen can reach the current density of 10 mA CM-2 with a low potential of 231mV, and maintains the stability of up to 225 hours, which significantly improves the activity and stability of the catalyst. sex.
Smart Images

Figure CN119372697A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electrocatalysis, and in particular to a novel protonated layered iridium oxide H-IrO2 nanosheet and a preparation method and application thereof. Background Art
[0002] Large-scale production of hydrogen through proton exchange membrane water electrolysis is one of the mature commercial hydrogen production technologies. This technology has the advantages of high current density, high hydrogen purity, and fast response speed. However, the strong acidic environment and high oxidation potential limit the selection of anode catalyst materials. Iridium oxide is widely used as an anode catalyst for water splitting reaction due to its excellent stability in acidic environment. Amorphous iridium oxide exhibits excellent catalytic activity but poor stability; on the contrary, rutile phase iridium dioxide (IrO2) has a stable rigid structure but insufficient catalytic activity. At present, it is still a challenge to achieve a balance between activity and stability in acidic oxygen evolution reaction (OER) catalysts, and there is still a lack of anode electrocatalysts with excellent performance to meet the needs of industrial-scale water electrolysis.
[0003] Layered iridium oxides show good catalytic potential due to their unique structure and properties, which are different from rutile phase and amorphous structure. Willinger et al. found that a high proportion of edge- and corner-sharing IrO6 octahedra is a key structural feature that significantly enhances the acidic OER activity. Traditionally, layered iridium oxides are synthesized by long-term high-temperature calcination to obtain materials with high crystallinity and large particle size. Due to limited surface area and lack of active sites, their direct activity as acidic OER catalysts is unsatisfactory. Intercalation exfoliation and the introduction of proton exchange are used to prepare ultrathin or monolayer iridium oxide nanosheets, which have higher activity than rutile phase IrO2 due to their enlarged surface area and rich defects. The reduced structural stability may come from the large number of structural defects generated by exfoliation, which weakens the intralayer connection and reduces the stability of active sites. Therefore, integrating long-range order and local defects into the crystal structure of the same catalytic system is crucial to optimize catalyst activity and stability, and it is also a very challenging research topic. Summary of the invention
[0004] The technical problem to be solved by the present invention is to overcome the deficiencies of the prior art and provide a protonated layered iridium oxide H-IrO2 nanosheet having both high activity and high stability and a preparation method and application thereof.
[0005] As one aspect of the present invention, the present invention provides a protonated layered iridium oxide H-IrO2 nanosheet, wherein the iridium oxide nanosheet has a layered structure, wherein the layered structure contains protons between layers, and wherein the layered structure has metal iridium vacancy defects within the surface. In the present invention, in the layered structure of iridium oxide, the octahedral units within the layer have stable connections, wherein local defects provide a large number of active sites for it. The open interlayer space and abundant edges further increase the exposed surface area, which is conducive to efficient mass transfer and reaction.
[0006] As a second aspect of the present invention, the present invention also provides a method for preparing the above-mentioned protonated layered iridium oxide H-IrO2 nanosheets, by adopting a fast and gentle Joule heating process combined with a proton exchange process to prepare iridium oxide with long-range ordered connections and local disordered defects. This synthesis method avoids long-term high-temperature calcination or time-consuming intercalation and stripping, promotes protonation and defect construction, and also avoids the instability problem caused by too many defects.
[0007] Specifically, the preparation method of the present invention comprises the following steps: 1) Iridium metal salt is hydrolyzed in an alkaline solution to obtain an amorphous iridium oxide precursor; 2) subjecting the amorphous iridium oxide precursor iridium to Joule heating to obtain layered iridium oxide nanosheets; 3) The layered iridium oxide nanosheets are subjected to a proton exchange reaction in an acidic solution to obtain protonated layered iridium oxide nanosheets.
[0008] Furthermore, in the iridium metal salt, IrCl4 2- The concentration is 0.0001-0.0005 mol / L, and the solution pH is 10~14.
[0009] Furthermore, the Joule heating reaction is performed by heat treatment at a constant temperature of 300-900° C. for 0.5-60 seconds.
[0010] Furthermore, the acidic solution has a pH of 0≤pH≤5 and a treatment time of 6-24 hours.
[0011] As a third aspect of the present invention, the present invention also provides an application of the above-mentioned protonated layered iridium oxide nanosheets as an electrocatalyst for oxygen evolution reaction. The synergistic effect of the layered structure, interlayer protons and surface defects of the protonated layered iridium oxide nanosheets makes the iridium oxide H-IrO2 nanosheets as a catalyst show excellent activity and stability in electrochemical tests. The excellent catalytic stability comes from the stable Ir-Ir connection in the layered structure and the highly reversible stretching characteristics of the Ir-O bond in the IrO6 octahedral unit during the OER process. The structural flexibility and robustness of the protonated layered iridium oxide achieve a synergistic improvement in catalyst activity and stability. Therefore, this catalyst structure that combines flexibility and stability provides more options for industrial water electrolysis oxygen evolution catalysts.
[0012] Compared with the prior art, the advantages of the present invention are: 1. The protonated layered iridium oxide nanosheet catalyst of the present invention only needs a low overpotential of 231 mV to reach 10 mA cm in the electrochemical oxygen evolution reaction. -2 .
[0013] 2. The protonated layered iridium oxide nanosheet catalyst of the present invention maintains 10 mA cm -2 The oxygen evolution reaction was stable for 225 hours at high current density without obvious activity decay.
[0014] 3. In the assembled membrane electrode electrolyzer, the prepared electrode is -2 Good activity can be maintained for up to 120 h at high current density, which indicates the high stability of the prepared electrode.
[0015] 4. The excellent activity and stability of the oxygen evolution catalyst of the present invention make it possible to apply it in industrial applications of actual large-current acidic water electrolysis. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 These are electron microscope images of protonated layered iridium oxide nanosheets, where a is a scanning electron microscope image, and bd are high-magnification transmission electron microscope images of the local structure of the material.
[0017] Figure 2 This is a composition analysis of protonated layered iridium oxide nanosheets, where Figure a is a thermogravimetric analysis diagram, and Figures b and c are the X-ray photoelectron spectra of metallic iridium and oxygen, respectively.
[0018] Figure 3 The scanning rate of protonated layered iridium oxide nanosheets as catalyst in acidic water electrolysis system (0.5 mol / L H2SO4) was 5 mV s -1 Comparison of cyclic voltammetry curves at 10 mA cm-2 Constant current test under current density (Figure c), Figure b is the curve of current density changing with time under high current density in the membrane electrode electrolyzer.
[0019] Figure 4 This is the electrochemical in situ X-ray absorption spectrum of protonated layered iridium oxide nanosheets and rutile phase iridium dioxide. DETAILED DESCRIPTION
[0020] The present invention is further described below in conjunction with specific preferred embodiments, but the protection scope of the present invention is not limited thereby.
[0021] Embodiment 1: (1) Preparation of iridium oxide precursor: Dissolve iridium chloride in ethanol solution, then add 1 mol / L KOH solution. In the final solution system, IrCl4 2- The concentration is 0.0005 mol / L, and the solution pH is 14; the mixture is stirred and heated for 5 hours. After the solvent is completely evaporated, the sample powder is collected for later use.
[0022] (2) Preparation of layered iridium oxide nanosheets by Joule heating: Take an appropriate amount of precursor powder and place it on a Joule heating device, spread it evenly, and heat it at 900 °C for 0.5 seconds. After the reaction is completed, wait for natural cooling, take out the powder sample, wash it with deionized water and ethanol respectively, and centrifuge it, and dry it in an oven at 60 degrees for later use.
[0023] (3) Protonated layered iridium oxide nanosheets were obtained by proton exchange: the dried layered iridium oxide nanosheet powder was placed in a sulfuric acid solution (pH 0), allowed to stand for 6 hours, and then washed and centrifuged with deionized water and ethanol respectively, and dried in an oven at 60 degrees for later use, which is hereinafter referred to as H-IrO2 catalyst.
[0024] (4) As a comparison, we heated and calcined the H-IrO2 catalyst at 600 °C in a tubular furnace for 2 h to obtain a sample of rutile phase iridium dioxide, hereinafter referred to as R-IrO2 catalyst.
[0025] Morphology and structural characterization: Scanning electron microscopy images show that the lateral size of H-IrO2 catalyst nanosheets reaches the micrometer level, overlapping each other to form a three-dimensional structure ( Figure 1a). Since the ultrathin layered nanosheets are sensitive to electrons, low-dose transmission electron microscopy was used for morphological and structural characterization. The high-angle annular dark field scanning transmission electron microscopy (HAADF-STEM) image shows a clear layered structure with an interlayer spacing of approximately 0.46 nm (Figure 1b). The differential phase contrast scanning transmission electron microscopy (iDPC-STEM) image in Figure 1c observed crystallographic features with long-range order. In addition, disordered regions within the layer and defects such as metal vacancies can also be observed, as shown in the dotted circles (Figure 1d). These defects may be caused by alkali metal ions occupying these positions during Joule heating and then being removed during ion exchange. At the same time, the distance between adjacent Ir atoms was measured to be 0.315 nm.
[0026] We used thermogravimetric analysis (TGA) to study the temperature dependence of the mass of protonated layered iridium oxide ( Figure 2 a). Weight loss below 200 °C mainly reflects the release of adsorbed water. After reaching 1000 °C, the continued weight loss is the removal of structural water and hydroxide ion species, which corresponds to the loss of protons in the layered structure and the phase transformation of H-IrO2 into the thermally stable rutile structure (R-IrO2). Weight loss above 1000 °C is due to the release of oxygen to form metallic iridium. Surface analysis of the elemental oxidation states of layered iridium oxide and rutile IrO2 was performed. High-resolution XPS spectra of Ir 4f ( Figure 2 b) shows that H-IrO2 contains Ir 3+ (62.2 eV), Ir in R-IrO2 4+ (62.0 eV). Oxygen species analysis showed that the proportion of hydroxyl groups on the surface of H-IrO2 was significantly higher than that of R-IrO2 (Figure 2c). These results suggest that the protons in H-IrO2 effectively share the positive charge of Ir by forming hydroxyl groups with oxygen, enriching the surface with hydroxyl and Ir sites and reducing their oxidation state.
[0027] Electrochemical performance test: Room temperature electrochemical test was carried out using a three-electrode system on a Shanghai Chenhua CHI760E electrochemical workstation. The prepared H-IrO2 catalyst powder-loaded carbon paper was used as the working electrode, the Hg / Hg2SO4 electrode (the electrolyte was saturated potassium sulfate) was used as the reference electrode, and the platinum sheet electrode was used as the counter electrode. The electrolyte was 0.5 M H2SO4. The scan rate was 5 mV s -1 Linear voltammetry was performed. All polarization curves were subjected to 95% ohmic compensation. -2 The electrolysis was continued for 225 hours under the same conditions to investigate the stability of the electrocatalyst. -2The oxygen evolution test was carried out for 120 hours under the conditions of
[0028] The OER electrocatalytic performance of the two iridium oxides was evaluated in 0.5 M H2SO4 acidic electrolyte. H-IrO2 only required an overpotential of 231 mV to reach 10 mA cm -2 The current density of H-IrO2 is 10 mA cm -2 The H-IrO2 phase exhibited long-term stability for up to 225 hours at a current density of 1 A cm, while the rutile phase lasted less than 70 hours before its activity gradually decreased (Figure 3c). To further evaluate the industrial potential of H-IrO2, a high current density (1 A cm -2 ) Performance test under working conditions. As shown in Figure 3b, H-IrO2 can maintain excellent stability for up to 120 hours.
[0029] In situ X-ray absorption spectroscopy (XAS) was used to monitor and characterize the changes in the oxidation state and coordination environment of the metallic iridium sites during the OER process to further elucidate the potential structure-performance relationship. A series of XAS spectra were recorded as the applied potential was sequentially increased from open circuit potential (OCP), 1.2 V, 1.35 V to 1.5 V vs. RHE, and then symmetrically reduced back to OCP. For H-IrO2, the white line peak position shifted to higher energy with increasing applied potential ( Figure 4 a), indicating that Ir is oxidized to a higher valence state, with the highest oxidation state exceeding Ir +4 In contrast, the position of the white line of R-IrO2 did not change significantly ( Figure 4 b), indicating that the Ir sites in the rutile phase are not easily affected by protonation and oxidation, thus showing good structural stability but unsatisfactory activity. Figure 4 c It can be seen that the change in the Ir-O bond length in H-IrO2 is negatively correlated with the applied potential. When the applied potential is reversed, the bond length returns to its initial state. In contrast, the Ir-O bond length in R-IrO2 remains essentially unchanged ( Figure 4d). In addition, the change in Ir-Ir distance is associated with a certain degree of distortion of the IrO6 octahedral arrangement. In situ observation of the Ir-Ir coordination environment showed that the Ir-Ir bonds in the second coordination shell of H-IrO2 hardly changed during the application and removal of potential (Figure 4c), confirming the overall stability of the connections between co-edge IrO6 octahedra in the layered structure. This means that the structural perturbations at high applied potentials are limited to the IrO6 octahedral units, while the overall structural integrity is maintained. In the rutile phase, the Ir-Ir bond extension at 1.5 V vs. RHE indicates an increase in disorder at elevated oxidation potentials (Figure 4d). Although the bond lengths return to their original values after the potential is reduced, prolonged operation at high potentials may gradually destroy the structural integrity of R-IrO2. Therefore, the dynamic structural changes of Ir-O bonds, combined with the rigid connections of IrO6 units in the two-dimensional framework H-IrO2, synergistically promote its enhanced activity and stability.
[0030] Embodiment 2: (1) Preparation of iridium oxide precursor: Dissolve iridium chloride in ethanol solution, then add 1 mol / L KOH solution. In the final solution system, IrCl4 2- The concentration is 0.0001 mol / L, and the solution pH is 10; the mixture is stirred and heated for 5 hours. After the solvent is completely evaporated, the sample powder is collected for later use.
[0031] (2) Preparation of layered iridium oxide nanosheets by Joule heating: Take an appropriate amount of precursor powder and place it on a Joule heating device, spread it evenly, and heat it at 300 °C for 60 seconds. After the reaction is completed, wait for natural cooling, take out the powder sample, wash it with deionized water and ethanol respectively, and centrifuge it, and dry it in an oven at 60 degrees for later use.
[0032] (3) Obtaining protonated layered iridium oxide nanosheets by proton exchange: The dried layered iridium oxide nanosheet powder was placed in a sulfuric acid solution (pH 5), allowed to stand for 24 hours, and then washed and centrifuged with deionized water and ethanol respectively, and dried in an oven at 60 degrees for later use, hereinafter referred to as H-IrO2 catalyst.
[0033] (4) As a comparison, we heated and calcined the H-IrO2 catalyst at 600 °C in a tubular furnace for 2 h to obtain a sample of rutile phase iridium dioxide, hereinafter referred to as R-IrO2 catalyst.
[0034] The test results were tested according to the test method of Example 1. The results showed that the product obtained in this example had a typical layered structure, and the layer contained long-range ordered regions and local defects. The catalytic performance test was further carried out according to the test method of Example 1. The results showed that the obtained layered protonated iridium oxide had excellent catalytic activity at 10 mA cm -2The overpotential is about 235mV.
[0035] The above is only a preferred embodiment of the present application and does not constitute any form of limitation to the present application. Although the present application is disclosed as a preferred embodiment as above, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A protonated layered iridium oxide H-IrO2 nanosheet, characterized in that: The iridium oxide nanosheet has a layered structure, protons are accommodated between layers of the layered structure, and metal iridium vacancy defects are present within the surface of the layered structure.
2. A method for preparing protonated layered iridium oxide H-IrO2 nanosheets as claimed in claim 1, characterized in that: The following steps are involved: Alkaline hydrolysis of iridium metal salt to obtain an amorphous iridium oxide precursor; Performing Joule heating treatment to obtain layered iridium oxide nanosheets; Acidic proton exchange yields protonated layered iridium oxide nanosheets.
3. The method for preparing protonated layered iridium oxide H-IrO2 nanosheets according to claim 2, characterized in that: In alkaline hydrolysis system, IrCl4 2- The concentration is 0.0001-0.0005 mol / L, and the solution 14≥pH≥10.
4. The method for preparing protonated layered iridium oxide H-IrO2 nanosheets according to claim 2, characterized in that: The Joule heating reaction is performed by heat treatment at a constant temperature of 300-900° C. for 0.5-60 seconds.
5. The method for preparing protonated layered iridium oxide H-IrO2 nanosheets according to claim 2, characterized in that: The acidic solution has a pH of 0≤pH≤5 and a treatment time of 6-24 hours.
6. Use of the protonated layered iridium oxide H-IrO2 nanosheets as claimed in claim 1 as an electrocatalyst for oxygen evolution reaction in acidic water electrolysis.
Citation Information
Patent Citations
Layered iridium-based perovskite nanosheet catalyst, preparation method and application of layered iridium-based perovskite nanosheet catalyst in electro-catalysis oxygen evolution reaction
CN114606510A
Nano iridium oxide catalyst as well as preparation method and application thereof
CN115849469A
Preparation method of uniform small-size PEMWE anodic iridium oxide catalyst
CN115959722A
Ultrathin honeycomb layered oxide nanosheet, preparation method and application of ultrathin honeycomb layered oxide nanosheet in electrocatalytic acidic oxygen evolution reaction
CN116375113A
Ruthenium monatomic doped metastable state iridium oxide catalyst as well as preparation method and application thereof
CN116695140A
Cited By
Preparation method of manganese-doped nickel sulfide / porous foamed nickel electrode for bifunctional alkaline electrolytic water
CN120138693A
A preparation method of a bifunctional alkaline electrolytic water manganese-doped nickel sulfide / porous nickel foam electrode
CN120138693B
A precursor-induced morphology-regulated iridium oxide electrocatalyst and a preparation method thereof
CN122667647A